Virtual reality therapy for anxiety : a guide for therapists - McMahon, Elizabeth; Boeldt, Debra (New York, NY : Routledge, 2022)
"Practical, down to earth, clearly written, and easy for therapists to understand and apply, Virtual Reality Therapy for Anxiety is a useful guide for any clinician treating anxiety, regardless of setting (in-office or via telehealth), theoretical orientation, or level of training. Written by an experienced psychologist who has used multiple VR systems since 2010, it's the only up to date, clinically informed, evidence-based training manual available. Easy-to-understand concepts and diagrams explain anxiety and its treatment, and the book incorporates research findings and clinical expertise. VRT is described step by step with multiple case examples, and an extended case-vignette chapter presents a session-by-session treatment protocol of a complex case with transcript excerpts. Key findings and quotations from research are also presented. After completing the guide, therapists and other mental health professionals will understand the unique clinical benefits of VR, be prepared to use VR in therapy comfortably and effectively either in the office or remotely, and will have expertise in a new, needed, and empirically validated treatment for a common clinical problem"--
Keywords: Anxiety -- Treatment; Virtual reality therapy; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health